A Philosophy of Practising: With Deleuze's Difference and Repetition, Antonia Pont (2021). Issue 1 (1st July 2022) - Hawkins, Kat
Review of: A Philosophy of Practising: With Deleuze's Difference and Repetition, Antonia Pont (2021)Edinburgh: Edinburgh University Press Ltd, 350 pp., ISBN 978-1-47449-046-7, h/bk, £80.00